The relationship between the housing & labor market crises and doubling-up: An MSA-level analysis, 2005-2010 - William H. Rogers; Anne E. Winkler (Institute for the Study of Labor (IZA), 2013)
It is now well-established that the U.S. housing market crisis preceded the labor market crisis and that, in the wake of these crises, doubling-up and cohabitation increased and homeownership fell. What is less clear is what happened at the subnational level. This study reports on: 1) how the length, severity and relative timing of both the labor market and housing crises varied by MSA; and 2) the association between the timing of the labor market and housing crises and changes in homeownership and doubling-up at the MSA level. The analysis is conducted using data on 353 MSAs, with a focus on 12 MSAs, for the period 2005 (pre-crisis) through 2010/2011. MSAs are categorized into those where the housing market declined first, those where the labor market declined first, and those where the events were concurrent. The analysis reveals that: 1) in the majority of MSAs, the labor market declined first, contrary to the national pattern and the experience of the vast majority of large MSAs; 2) there is a clear relationship between greater regional housing distress and falling homeownership rates; and 3) somewhat surprisingly, the association between changes in doubling-up and these crises are fairly weak at the MSA level.
Keywords: R23; J12; 330; labor market; housing market; foreclosures; household formation